AMIR TEMUR AND THE PERIOD OF THE TEMURIDS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract explores the enduring legacy of Amir Timur and the Timurid period, focusing on their impact on Central Asia and beyond during the 14th and 15th centuries. Amir Timur, also known as Tamerlane, rose from humble beginnings to become a formidable conqueror whose military campaigns reshaped the geopolitical landscape of Eurasia. The Timurid Empire, established by Timur, became a hub of cultural exchange and artistic innovation, exemplified by the architectural marvels of Samarkand and the intellectual achievements of Timurid scholars. The abstract delves into the multifaceted contributions of the Timurids, emphasizing their synthesis of Persian, Turkic, and Mongol traditions that fostered a vibrant cultural renaissance. Timur's patronage of learning and the arts laid the groundwork for a period of flourishing intellectual activity, transforming the Timurid capital into a center of scholarship and creativity. Furthermore, the abstract highlights the enduring impact of the Timurid legacy on subsequent empires and dynasties in the region, illustrating how Timur's vision of empire-building and cultural exchange left an indelible mark on the course of history. The abstract concludes by underscoring the significance of Amir Timur and the Timurids as pivotal figures in the development of Central Asia and the wider Islamic world, whose influence continues to resonate in contemporary discourse on art, culture, and historical scholarship.